DEM simulation of internal erosion around a submerged defective pipe. Issue 2 (October 2020) - Wu, Binzhong; Yan, Qiong; Wang, Li; Chen, Quansheng; Wang, Tuo; Zhang, Fengshou
Abstract: Internal erosion caused by broken sewer pipes often leads to ground subsidence in urban area, which is a major risk to public safety and has caused substantial socioeconomic loss. In order to ensure the ground stabilization and the safety of buried pipelines, it is necessary to understand the process of internal erosion around a submerged defective pipe. In this paper, the Dynamic Fluid Mesh (DFM) is coupled with the three-dimensional discrete element method (DEM) to simulate internal erosion in gap-graded soils above a defective pipe. In this fluid-solid coupling scheme, the fluid mesh can be generated according to the soil skeleton formed by coarse particles and updated at regular intervals. Seepage forces are calculated and applied on solid particles in the DEM model. The approach accounts for permeability and porosity changes due to soil skeleton deformation and internal erosion. In this study, some gap-graded soils samples with different size ratio are established. A defective pipe is placed below the sample. After that, different hydraulic gradients are applied to the sample. Fine particles are washed away from the hole in the pipe. The results indicate that the erosion process can be divided into three stages according to changes in the erosion rate. In the initial stage, numerous fine particles are washed away, and the flow rate increases with the increase of eroded particles. Subsequently, the erosion rate decreases and the flow rate tends to reach a steady state. Finally, only a small proportion of particles fall down from the outlets and the erosion rate levels off to zero gradually. Parametric studies show that the increase of hydraulic gradient increase the eroded particle mass. The number of erosion particles from the bottom layer is much larger than those from the upper layers as more fine particles in the upper layers are locked.